The Ring of Dancers : Images of Faroese Culture - Wylie, Jonathan (South Asia Seminar, 2016)
The Ring of Dancers is composed a series of studies of aspects of Faroese life, language, and folk ways. A recurrent theme is the continuing reformulation of Faroese culture since the islands' Viking settlement in the ninth century.